Configuração espacial da geografia alimentar em Sergipe - Sônia de Souza Mendonça Menezes; Paulo Adriano Santos Silva; Heberty Ruan Conceição Silva (Confins)
The heterogeneity of food grown in Sergipe is based on the intrinsic relation with family agriculture, however, some products are also grown in medium and large rural establishments. The actions of the Brazilian State, through public policies and government programs, in line with the actions of the different government agencies of Sergipe, directly influenced the strengthening of the different food producing branches. The objective of this article is to analyze the current spatial configuration of food production, based on the main foodstuffs produced in the state. To do so, we will analyze the historical trajectory and current dynamics of the production of fruits, grains, tubers, milk, cheeses and pigs; besides identifying the spatial distribution of these foods in the Sergipe territory. As methodological procedures, we base our analyzes in the theoretical debates, in the databases and in the field researches developed by the Grupo de Estudo e Pesquisa Sobre Alimentos e Manifestações Tradicionais - GRUPAM. As results, we show that the production of food in Sergipe presents in a complex and heterogeneous way, mixing family production and agribusiness, different flavors, forms of production, commercialization and consumption, a tangle of relations that configure the geography of production of food from Sergipe.